PENGARUH NILAI REKREDENSIALING TERHADAP KEPUASAN PESERTA BPJS DIFASILITASKESEHATANTINGKATPERTAMA(FKTP)BANDARLAMPUNG - Hakim, Amri; Nurbaiti, Nurbaiti; Pratiwi, Ariska (Jurnal Jejama Manajemen Malahayati, 2022)
This study aims to dtermine the effect of the value of credentialing on the satisfaction of BPJS participants at First Level Health Facilities (Fktp) Bandar Lampung. This study uses quantitative datathat can be measured or calculated directly. The sources of research data are primary data obtaineddirectly from the source location and object of research without going through intermediaries. Thisprimary data collection method was carried out using a questionnaire method which was distributed torespondents. Based on the results of the research conducted, that the value of recredensailing with the variablesof human resources, facilities and infrastructure,home visits, medical equipment, medicinesand complaints handling, scope of service, service commitment. Simultaneously has a positive effect onparticipant satisfaction. This means that the better the recredentialing value of a first-level health facility(FKTP) will affect participant satisfaction.Keywords:FirstLevelHealthFacilities,ParticipantSatisfaction, Recredentialing